Anode and method for producing same

A dual-layer structure for negative electrodes in lithium secondary batteries, featuring primary particles with high binder content in the lower layer and secondary particles with a carbon coating in the upper layer, addresses adhesive strength and rapid charging issues, enhancing battery performance by optimizing binder distribution and reducing resistance.

JP7612857B2Active Publication Date: 2025-01-14LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023523167
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2021-10-15
Publication Date
2025-01-14
Estimated Expiration
2041-10-15

AI Technical Summary

Technical Problem

Conventional methods for manufacturing negative electrodes in lithium secondary batteries fail to adequately address the issue of adhesive strength and rapid charging performance due to the presence of fine powder and non-uniform pores, leading to decreased adhesion and increased resistance, which is exacerbated by the use of carbon coating layers that do not effectively suppress fine powder detachment.

Method used

A dual-layer structure for the negative electrode is introduced, where the lower layer contains primary particles of artificial graphite with a higher binder polymer content and the upper layer contains secondary particles of artificial graphite with a carbon coating layer and a lower binder polymer content, optimizing the distribution and adhesion properties.

Benefits of technology

This approach enhances the adhesive strength between the active material layer and the current collector while improving rapid charging performance by ensuring uniform binder distribution and reducing resistance, thereby improving the overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612857000001
    Figure 0007612857000001
  • Figure 0007612857000002
    Figure 0007612857000002
Patent Text Reader

Abstract

The present invention discloses an anode comprising: an anode current collector; and an anode active material layer including: a lower layer region located on at least one surface of the anode current collector and including a first active material and a first binder polymer; and an upper layer region located in the lower layer region and including a second active material and a second binder polymer, wherein the first active material is primary particles of artificial graphite; the second active material comprises secondary particles of artificial graphite and a carbon coating layer located on the secondary particles; and the weight percentage of the first binder polymer in the lower layer region is greater than the weight percentage of the second binder polymer in the upper layer region. The present invention also discloses a method for manufacturing the anode; and a lithium secondary battery including the anode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode that ensures adhesion and improves rapid charging performance, and a method for producing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0134666, filed on October 16, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] As technological development and demand for mobile devices increases, the demand for rechargeable, compact, and high-capacity secondary batteries is rapidly increasing. Among secondary batteries, lithium secondary batteries, which have high energy density and voltage, have been commercialized and are widely used.

[0004] A lithium secondary battery is constructed by impregnating an electrolyte containing a lithium salt in an electrode assembly having a porous separator between a positive electrode and a negative electrode, each of which is coated with an active material on an electrode collector. The electrode is manufactured by applying a slurry, in which the active material, a binder, and a conductive material are dispersed in a solvent, to a current collector, followed by drying and pressing.

[0005] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and extracts lithium ions from the positive electrode. The negative electrode active material may be a graphite-based active material, such as natural graphite or artificial graphite.

[0006] The artificial graphite is mainly used in the form of secondary particles, and for this purpose, coke, which is a material for primary particles, is generally coarsened to produce secondary particles, which are then graphitized by heat treatment to obtain artificial graphite in the form of secondary particles.

[0007] However, in the case of the conventional manufacturing method in which the size of the primary particles is not controlled, a large amount of fine powder that is not coarsened or that is separated from the secondary particles even after coarsening is generated. This reduces the negative electrode adhesive strength (resistance to the negative electrode active material particles being detached from the negative electrode) in the manufactured negative electrode, which may deteriorate the high-temperature storage performance of the battery. In addition, since the fine powder is also contained in the secondary particles, the pores of the negative electrode are not uniform, which increases the pore resistance of the negative electrode, thereby deteriorating the fast charging performance of the battery.

[0008] In the past, a process of disposing a carbon coating layer on the secondary particles has been used to solve these problems. However, the carbon coating layer alone is not able to suppress the detachment of fine powder, and the degree of improvement in effect is minimal. Even if the detachment is suppressed, the fine powder present in the secondary particles cannot be removed, making it difficult to improve the fast charging performance of the battery. In addition, the only way to solve the problems caused by the excessive content of fine powder is to increase the content of pitch used in the granulation process or carbon precursor required for forming the carbon coating layer, which reduces the capacity per weight of the negative electrode.

[0009] Meanwhile, in existing commercial batteries, the negative and positive electrodes are formed by coating the electrode slurry once on each electrode collector. In this case, when the binder distribution in the cross section of the electrode layer is measured, the binder content is high near the surface and decreases toward the current collector.

[0010] In such electrodes, the adhesion strength is reduced due to a reduction in the binder content near the current collector, and when the binder content is increased to improve the problem of reduced adhesion, the resistance increases and the fast charging performance is reduced.

[0011] Therefore, a method is required to improve the adhesive strength between the active material layer of the electrode and the current collector and to improve the fast charging performance of the battery. Summary of the Invention [Problem to be solved by the invention]

[0012] The present invention has been made in consideration of the above problems, and has an object to provide a negative electrode that ensures adhesive strength and improves rapid charging performance, and a method for producing the same.

[0013] Another object of the present invention is to provide a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0014]

[0013] In order to achieve the above object, according to one aspect of the present invention, there is provided a method for manufacturing a negative electrode according to the following embodiment.

[0015] According to one embodiment of the present invention, A negative electrode current collector; a negative electrode active material layer including: a lower layer region located on at least one surface of the negative electrode current collector and including a first active material and a first binder polymer; and an upper layer region located in the lower layer region and including a second active material and a second binder polymer; the first active material is a primary particle of artificial graphite, the second active material is a secondary particle of artificial graphite and a carbon coating layer located on the secondary particle, A negative electrode is provided, characterized in that the weight percentage of the first binder polymer in the underlayer region is greater than the weight percentage of the second binder polymer in the overlayer region.

[0016] According to the second embodiment, in the first embodiment, the first active material may have a D50 of 3 μm to 20 μm.

[0017] According to a third embodiment, in the first or second embodiment, the second active material may have a D50 of 5 μm to 35 μm.

[0018] According to a fourth embodiment, in any one of the first to third embodiments, the secondary particles of artificial graphite may be formed by granulating the primary particles of artificial graphite.

[0019] According to a fifth embodiment, in any one of the first to fourth embodiments, the carbon coating layer of the second active material may be included in an amount of 0.5 wt % to 10.0 wt % based on the total weight of the second active material.

[0020] According to a sixth embodiment, in any one of the first to fifth embodiments, the ratio of the weight percentage of the first binder polymer in the lower layer region to the weight percentage of the second binder polymer in the upper layer region may be 1.1:1 to 5:1.

[0021] According to the seventh embodiment, in any one of the first to sixth embodiments, the ratio (wt%) of the first binder polymer in the lower layer region of the negative electrode active material layer may be 2 to 4 wt%, and the ratio (wt%) of the second binder polymer in the upper layer region of the negative electrode active material layer may be 0.5 to 2 wt%.

[0022] According to an eighth embodiment, in any one of the first to seventh embodiments, the total weight percentage (wt%) of the first binder polymer and the second binder polymer may be 1 to 3 wt% based on the entire negative electrode active material layer.

[0023] According to the ninth embodiment, preparing a lower layer slurry including a first active material, a first binder polymer, and a first dispersion medium, and an upper layer slurry including a second active material, a second binder polymer, and a second dispersion medium; coating one surface of a negative electrode current collector with the lower layer slurry, and coating the upper layer slurry on the lower layer slurry; and drying the coated lower layer slurry and the coated upper layer slurry simultaneously to form a negative electrode active material layer. the first active material is a primary particle of artificial graphite, the second active material is a secondary particle of artificial graphite and a carbon coating layer located on the secondary particle, The method for producing a negative electrode is characterized in that the weight percentage of the first binder polymer in the solid content of the lower layer slurry is greater than the weight percentage of the second binder polymer in the solid content of the upper layer slurry.

[0024] According to a tenth embodiment, in the ninth embodiment, the ratio of the weight % of the first binder polymer in the solid content of the lower layer slurry to the weight % of the second binder polymer in the solid content of the upper layer slurry may be 1.1:1 to 5:1.

[0025] According to an eleventh embodiment, in any one of the ninth to tenth embodiments, the weight percentage of the first binder polymer in the solid content of the lower layer slurry may be 2 to 4 weight%, and the weight percentage of the second binder polymer in the solid content of the upper layer slurry may be 0.5 to 2 weight%.

[0026] According to the twelfth embodiment, in any one of the ninth to eleventh embodiments, The total ratio (wt %) of the first binder polymer and the second binder polymer to the total solid content of the lower layer slurry and the upper layer slurry may be 1 to 3 wt %.

[0027] In a thirteenth embodiment, there is provided a lithium secondary battery including the negative electrode according to any one of the first to eighth embodiments. Effect of the Invention

[0028] According to an embodiment of the present invention, it is possible to provide a negative electrode having improved resistance characteristics by increasing the adhesive strength between a negative electrode active material layer and a current collector without significantly increasing the binder content and preventing the detachment of the active material.

[0029] Furthermore, when the same binder is applied throughout, the adhesive strength can be improved by increasing the proportion of the binder in the lower layer, and the fast charging performance can be improved by decreasing the proportion of the binder in the upper layer. In addition, the adhesive strength can be doubled by applying primary particle artificial graphite to the lower layer, and the fast charging performance can be further improved by applying secondary particle artificial graphite with a carbon coating layer to the upper layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, preferred embodiments of the present invention will be described in detail. Prior to this, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.

[0031] According to one aspect of the invention, A negative electrode current collector; a negative electrode active material layer including: a lower layer region located on at least one surface of the negative electrode current collector and including a first active material and a first binder polymer; and an upper layer region located in the lower layer region and including a second active material and a second binder polymer; the first active material is a primary particle of artificial graphite, the second active material is a secondary particle of artificial graphite and a carbon coating layer located on the secondary particle, A negative electrode is provided, wherein the weight percentage of the first binder polymer in the lower layer region is greater than the weight percentage of the second binder polymer in the upper layer region.

[0032] In the present invention, the types of active materials contained in the lower layer region and the upper layer region are different. In particular, the lower layer region of the negative electrode active material layer contains primary particles of artificial graphite in an active material (first active material), and the upper layer region of the negative electrode active material layer contains secondary particles of artificial graphite and an active material (second active material) including a carbon coating layer located on the secondary particles.

[0033] In the case of secondary particles, the binder polymer can be distributed in the gaps between the primary particles that make up the secondary particles, reducing the number of binder polymers that can actually exert adhesive strength, but in the case of primary particles, no such gaps exist, so all of the binder polymer added can contribute to adhesive strength. As a result, by including primary particle artificial graphite in the lower layer region of the negative electrode active material layer that directly faces the current collector, it is possible to significantly improve the adhesive strength between the current collector and the negative electrode active material layer.

[0034] The upper layer region of the negative electrode active material layer contains an active material (second active material) including secondary particles of artificial graphite formed by granulating primary particles of artificial graphite, and a carbon coating layer located on the secondary particles. Since secondary particles have low orientation [(I(004) / I(110)], rapid charging performance can be improved.

[0035] The artificial graphite is generally produced by carbonizing raw materials such as coal tar, coal tar pitch, and petroleum-based medium oil at 2,500°C or higher, and is used as an anode active material after such graphitization and particle size adjustment such as crushing and secondary particle formation. In the case of artificial graphite, crystals are randomly distributed within the particles, and it has a lower sphericity and a slightly pointed shape compared to natural graphite.

[0036] The artificial graphite used in one embodiment of the present invention may be mesophase carbon microbeads (MCMB), mesophase pitch-based carbon fiber (MPCF), artificial graphite graphitized in a block form, or artificial graphite graphitized in a powder form, which are commonly used commercially. The artificial graphite used may have a sphericity of 0.91 or less, preferably 0.6 to 0.91, and more preferably 0.7 to 0.9.

[0037] In this specification, D50, which will be described later, is the particle size at the 50% point of the cumulative particle number distribution by particle size, and can be referred to as the average particle size. That is, "particle size Dn" means the particle size at the n% point of the cumulative particle number distribution by particle size. Accordingly, D90 means the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 means the particle size at the 10% point of the cumulative particle number distribution by particle size.

[0038] The D50 and Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in diffraction pattern due to the particle size is measured, and the particle size distribution can be calculated. D10, D50, and D90 can be measured by calculating the particle diameters at the 10%, 50%, and 90% points of the cumulative particle number distribution according to the particle diameter in the measuring device.

[0039] In terms of particle size distribution, the first active material, i.e., artificial graphite (primary particles) may have a D50 of 3 μm to 20 μm, preferably 5 μm to 15 μm, and more preferably 7 μm to 13 μm. When the D50 of the primary particles satisfies this range, the primary particles are formed to have high graphitization, and the orientation index of the negative electrode active material particles is appropriately ensured, thereby improving the fast charging performance.

[0040] In the second active material, the secondary particles may be formed by granulating the primary particles, i.e., the secondary particles may be structures formed by agglomerating the primary particles together through a granulation process.

[0041] The second active material may include a carbon coating layer on a surface of the second particle, and the carbon coating layer may include at least one of amorphous carbon and crystalline carbon.

[0042] The crystalline carbon may further improve the conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0043] The amorphous carbon can appropriately maintain the strength of the coating layer and improve the output characteristics and fast charging performance of the artificial graphite. The amorphous carbon can be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source in a chemical vapor deposition process.

[0044] The other carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and combinations thereof.

[0045] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.

[0046] The carbon coating layer may be included in an amount of 0.5 wt % to 10.0 wt %, specifically, 1 wt % to 8 wt %, or 2 wt % to 6 wt %, based on the total weight of the second active material. When the amount is within the above range, the capacity per weight of the negative active material particles is ensured, while the fast charging performance of the artificial graphite can be improved.

[0047] The D50 of the second active material may be 5 μm to 35 μm, specifically 7 μm to 33 μm, and more specifically 10 μm to 30 μm. When the D50 satisfies the above range, the second active material is uniformly dispersed in the upper layer slurry, and the charging performance of the battery can be improved.

[0048] In the negative electrode of the present invention, since the first active material contained in the lower layer region and the second active material contained in the upper layer region have different average particle sizes and shapes, a mixed region (intermixing) in which these different types of active materials are mixed may exist at the portion where the lower layer region and the upper layer region come into contact with each other. This is because, when a negative electrode active material layer is formed by coating a lower layer slurry containing a first active material and an upper layer slurry containing a second active material simultaneously or successively with a very short time lag on a current collector and then drying them simultaneously, a certain mixed region is generated at the interface where the lower layer slurry and the upper layer slurry come into contact with each other before drying, and the mixed region is formed into a layer shape during subsequent drying.

[0049] In one embodiment of the present invention, the weight ratio (ratio of load per unit area) of the lower layer region to the upper layer region of the negative electrode active material layer may be 20:80 to 80:20, more specifically, 30:70 to 70:30. When this weight ratio range is satisfied, the adhesive strength is increased and excellent fast charging performance can be exhibited.

[0050] In an embodiment of the present invention, the thickness ratio of the upper layer region to the lower layer region may be 20:80 to 80:20, and more particularly, 30:70 to 70:30. When the thickness ratio is within this range, the adhesive strength is increased and excellent fast charging performance can be exhibited.

[0051] In an embodiment of the present invention, the total thickness of the negative electrode active material layer is not particularly limited and may be, for example, 40 to 200 μm. In addition, the thickness of the lower layer region of the negative electrode active material layer may be 20 to 150 μm or 30 to 100 μm, and the thickness of the upper layer region of the negative electrode active material layer may be 20 to 150 μm or 30 to 100 μm.

[0052] In this case, when the thicknesses of the upper layer region and the lower layer region satisfy this range, the adhesive strength is high and excellent fast charging performance can be exhibited.

[0053] The weight percentage of the first binder polymer in the lower layer region is greater than the weight percentage of the second binder polymer in the upper layer region.

[0054] Specifically, the ratio of the weight percentage of the first binder polymer in the lower layer region to the weight percentage of the second binder polymer in the upper layer region can be 1.1:1 to 5:1, or 1.2:1 to 4:1, or 1.5:1 to 3:1, or 2.1:1 to 3:1, or 2.3:1.7 to 3:1, or 2.7:1.3 to 3:1, or 2.3:1.7 to 2.7:1.3.

[0055] In this case, when the weight percentage of the first binder in the lower layer region and the weight percentage of the second binder in the upper layer region satisfy the above ranges, excellent adhesive strength and fast charging performance can be exhibited.

[0056] In an embodiment of the present invention, the ratio (wt%) of the first binder polymer in the lower layer region of the negative electrode active material layer may be 2 to 4 wt% or 2.3 to 3 wt%, and the ratio (wt%) of the second binder polymer in the upper layer region of the negative electrode active material layer may be 0.5 to 2 wt% or 1 to 1.7 wt%.

[0057] In an embodiment of the present invention, the total weight percentage (wt%) of the first binder polymer and the second binder polymer in the entire negative active material layer may be 1 to 3 wt%, 1 to 2 wt%, or 2 to 3 wt%.

[0058] The weight percentage of the first binder polymer in the lower layer region and the weight percentage of the second binder polymer in the upper layer region of the negative electrode according to an embodiment of the present invention can be calculated from the weight percentage of the binder in the total content of solids (active material, conductive material, binder, thickener) contained in the lower layer slurry and the upper layer slurry for producing the initial lower layer and upper layer of the negative electrode.

[0059] In addition, the weight percentage of the first binder polymer in the lower region and the weight percentage of the second binder polymer in the upper region of the negative electrode active material layer of the negative electrode according to an embodiment of the present invention may be indirectly measured by dyeing the binder polymer with a metal oxide capable of dyeing and then measuring the content of the dyed metal using energy dispersive X-ray spectroscopy. The metal oxide may be osmium tetroxide (OsO4), ruthenium tetroxide (RuO4), or the like.

[0060] According to an embodiment of the present invention, a cross section of the negative electrode active material layer is cut, and the first and second binder polymers contained in the lower and upper regions of the negative electrode active material layer are dyed with osmium tetroxide (OsO4), and the osmium atomic ratio of the dyed cross section of the negative electrode active material layer is measured using energy dispersive X-ray spectroscopy. The osmium atomic ratio of the surface of the electrode active material layer measured in this manner is correlated with the binder polymer content of the cross section of the negative electrode active material layer dyed with osmium tetroxide (OsO4), and the binder polymer content can be calculated from the value.

[0061] Specifically, the final manufactured negative electrode is prepared to a predetermined size, and the negative electrode is cut vertically to expose the cross section of the negative electrode active material layer. The sample is then placed in a container filled with OsO4 (osmium tetraoxide) and sealed for 1 to 5 hours. The negative electrode is then removed and placed in a vacuum oven to dry for 24 to 72 hours. The binder polymer contained in the negative electrode active material layer is then dyed using OsO4, and the binder polymer content of the cross section of the dyed negative electrode can be analyzed using energy dispersive X-ray spectroscopy.

[0062] For example, a negative electrode according to an embodiment of the present invention was prepared with a size of 1 cm x 1 cm, placed in a container filled with OsO4 and sealed, and after 3 hours, the negative electrode was removed and placed in a vacuum oven to dry for 48 hours. The binder polymer contained in the negative electrode active material layer was dyed with OsO4, and the binder polymer content on the surface of the negative electrode after dyeing was analyzed using energy dispersive X-ray spectroscopy. The atomic ratio of osmium on the surface of the negative electrode active material layer can be measured under the following conditions using X-Max80 and Extreme detector (Oxford).

[0063] [Table 1]

[0064] In one embodiment of the present invention, the negative electrode current collector used in the substrate forming the negative electrode active material layer is not particularly limited as long as it is conductive and does not induce chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc. may be used.

[0065] The thickness of the current collector is not particularly limited, but may be a commonly applied thickness of 3 to 500 μm.

[0066] The first binder polymer and the second binder polymer may each independently be various types of binder polymers such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HEP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butylene rubber (SBR), fluororubber, and various copolymers.

[0067] According to an embodiment of the present invention, the negative active material layer may further include a thickener that contributes to dispersion stability of the slurry. The first thickener included in the lower layer region and the second thickener included in the upper layer region may each independently be carboxymethyl cellulose (CMC), carboxyethyl cellulose, polyvinylpyrrolidone polyvinyl alcohol, starch, hydroxypropyl cellulose, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyacrylic acid, etc.

[0068] The negative electrode active material layer may further include a conductive material. The conductive material is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0069] According to one aspect of the invention, preparing a lower layer slurry including a first active material, a first binder polymer, and a first dispersion medium, and an upper layer slurry including a second active material, a second binder polymer, and a second dispersion medium; coating one surface of a negative electrode current collector with the lower layer slurry, and coating the upper layer slurry on the lower layer slurry; and drying the coated lower layer slurry and the coated upper layer slurry simultaneously to form a negative electrode active material layer. The first active material is a primary particle of artificial graphite, and the second active material includes secondary particles formed by granulating the primary particle of artificial graphite, and a carbon coating layer located on the secondary particles, The method for producing a negative electrode is characterized in that the weight percentage of the first binder polymer in the solid content of the lower layer slurry is greater than the weight percentage of the second binder polymer in the solid content of the upper layer slurry.

[0070] The active material (first active material, second active material), binder polymer (first binder polymer, second binder polymer), alternative thickener (first thickener, second thickener), conductive material, etc. contained in the lower layer slurry and the upper layer slurry are the same as those described above.

[0071] The first and second dispersion media may each independently be N-methylpyrrolidone, acetone, water, or the like.

[0072] In this case, a lower layer region of the negative electrode active material layer of the present invention is formed from the coated lower layer slurry, and an upper layer region of the negative electrode active material layer of the present invention is formed from the upper layer slurry.

[0073] According to one embodiment of the present invention, the lower layer slurry may be coated, and then the upper layer slurry may be coated on the lower layer slurry at the same time or after a predetermined time lag. In this case, an apparatus such as a double slot die may be used.

[0074] The step of simultaneously drying the coated lower layer slurry and the coated upper layer slurry to form the negative electrode active material layer may include simultaneously drying the coated lower layer slurry and the coated upper layer slurry to remove a dispersion medium in the slurry, rolling the slurry, and then vacuum drying the slurry to form the negative electrode active material layer.

[0075] In this case, the rolling may be performed by a method commonly used in the art, such as roll pressing, at a pressure of 1 to 20 MPa and a temperature of 15 to 30° C. In addition, the rolling may be performed under conditions such that the porosity of the electrode (active material layer) after rolling is 20 to 40%, or 25 to 35%, or 20 to 30%, or 30 to 40%.

[0076] The step of drying the coated slurry may be performed at, for example, 70 to 90° C., or 75 to 85° C., or 80 to 85° C. for 10 to 30 minutes, or 15 to 25 minutes, or 20 to 30 minutes, and the drying temperature and time can be appropriately adjusted depending on the type and content of the dispersion medium.

[0077] In addition, the dried slurry layer may be rolled and then vacuum dried at a temperature of 100 to 170°C, 120 to 150°C, or 130 to 150°C for about 3 to 10 hours or 5 to 8 hours, and the drying temperature and time may be appropriately adjusted depending on the type and content of the dispersion medium.

[0078] The ratio of the weight percentage of the first binder polymer in the solid content of the lower layer slurry to the weight percentage of the second binder polymer in the solid content of the upper layer slurry may be 1.1:1 to 5:1, or 1.2:1 to 4:1, or 1.5:1 to 3:1, or 2.1:1 to 3:1, or 2.3:1.7 to 3:1, or 2.7:1.3 to 3:1, or 2.3:1.7 to 2.7:1.3.

[0079] In this case, when the weight percentage of the first binder in the coated lower layer slurry and the weight percentage of the second binder in the coated upper layer slurry satisfy this range, excellent adhesive strength and fast charging performance can be exhibited.

[0080] The weight percentage of the first binder polymer in the solid content of the lower layer slurry may be 2 to 4 weight percent, or 2.3 to 3 weight percent, and the weight percentage of the second binder polymer in the solid content of the upper layer slurry may be 0.5 to 2 weight percent, or 1 to 1.7 weight percent.

[0081] The total ratio (wt %) of the first binder polymer and the second binder polymer to the total solid content of the lower layer slurry and the upper layer slurry may be 1 to 3 wt %, or 1 to 2 wt %, or 2 to 3 wt %.

[0082] Still another embodiment of the present invention relates to a lithium secondary battery including a negative electrode manufactured as described above. Specifically, the lithium secondary battery can be manufactured by injecting an electrolyte containing a lithium salt into an electrode assembly including a positive electrode, a negative electrode as described above, and a separator interposed therebetween.

[0083] The positive electrode can be manufactured by mixing a positive electrode active material, a conductive material, a binder, and a solvent to produce a slurry, and then directly coating the slurry on a metal current collector or casting it on another support and laminating the positive electrode active material film peeled from the support on the metal current collector.

[0084] As the active material used for the positive electrode, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, and LiNi 1-x-y-z Co x M1 y M2 z O2 (where M1 and M2 are each independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are each independently the atomic fraction of the oxide composition element, and 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 ≦ z < 0.5, 0 < x + y + z ≦ 1). It may include any one active material particle selected from the group consisting of or a mixture of two or more of these.

[0085] On the other hand, the same conductive material, binder, and solvent as those used in the manufacture of the negative electrode can be used.

[0086] The separator may be a conventional porous polymer film used in a conventional separator, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Also, an insulating thin film having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) in which a ceramic material is thinly coated on the surface of the separator. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used, but is not limited thereto.

[0087] The electrolytic solution contains a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt.

[0088] The lithium salt can be used without any limitation as long as it is one that is commonly used in electrolytes for secondary batteries. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 -, CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One selected from the group consisting of:

[0089] The organic solvent contained in the electrolytic solution may be any commonly used organic solvent without limitation. Representative examples include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfide, and tetrahydrofuran.

[0090] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate organic solvents, are preferably used since they are high-viscosity organic solvents and have a high dielectric constant, which makes it easy to dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, which is preferable.

[0091] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are typically included in electrolytes.

[0092] In the lithium secondary battery according to an embodiment of the present invention, a separator is disposed between a positive electrode and a negative electrode to form an electrode assembly, and the electrode assembly is placed in, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and then an electrolyte is injected to complete the secondary battery. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and the resultant product may be placed in a battery case and sealed to complete the lithium secondary battery.

[0093] According to an embodiment of the present invention, the lithium secondary battery may be of a stacked type, a wound type, a stacked / folded type, or a cable type.

[0094] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a plurality of battery cells. Preferred examples of the medium- to large-sized devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, and can be particularly useful in hybrid electric vehicles and new energy storage batteries, which are areas where high output is required.

[0095] The present invention will be described in detail below with reference to examples to aid in understanding the present invention. However, the embodiments according to the present invention can be modified in various ways, and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those with average knowledge in the art.

[0096] Example 1: Preparation of negative electrode <Production of Lower Layer Negative Electrode Slurry> Primary particles of artificial graphite having an average particle size (D50) of 10 μm were used as the first active material.

[0097] The first active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a first binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 95:1:3:1, and water was added to prepare a slurry for the lower layer.

[0098] <Production of upper layer negative electrode slurry> A second active material was prepared, which included artificial graphite in the form of secondary particles formed by granulating primary particles of artificial graphite, and a carbon coating layer disposed on the artificial graphite. In this case, in the second active material, the primary particles had a D50 of 10 μm, and the average particle size (D50) of secondary particles formed by granulating and agglomerating the primary particles was 20 μm. The carbon coating layer on the secondary particles was included in an amount of 4.0 wt % based on the total weight of the second active material. In this case, the average particle size (D50) of the secondary particles on which the carbon coating layer was formed was 21 μm.

[0099] The second active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 97:1:1:1, and water was added to prepare a slurry for the upper layer.

[0100] <Production of negative electrodes> Using a double slot die, the slurry for the lower layer was applied at 2.5 mAh / cm2 to one side of a copper (Cu) foil, which was a negative electrode current collector having a thickness of 10 μm. 2 After applying the slurry for the lower layer at a loading amount of 2.5 mAh / cm2, the slurry for the upper layer was applied on the applied slurry for the lower layer. 2 After the slurry coating, the slurry was dried at 80°C for 20 minutes to remove water from the slurry, and the dried slurry layer was rolled and then vacuum dried at about 130°C for 8 hours to prepare a negative electrode. The porosity of the prepared negative electrode was 30%.

[0101] The negative electrode thus produced had a double-layer structure of an upper layer region with a thickness of 50 μm and a lower layer region with a thickness of 50 μm, and was provided with a negative electrode active material layer with a total thickness of 100 μm.

[0102] Example 2: Preparation of the negative electrode The first active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a first binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 95.3:1:2.7:1, and water was added to prepare a lower layer slurry. The second active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96.7:1:1.3:1, and water was added to prepare an upper layer slurry. The negative electrode was manufactured in the same manner as in Example 1.

[0103] Example 3: Preparation of negative electrode The first active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a first binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 95.7:1:2.3:1, respectively, and water was added to prepare a lower layer slurry. The second active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96.3:1:1.7:1, and water was added to prepare an upper layer slurry. The negative electrode was manufactured in the same manner as in Example 1.

[0104] Comparative Example 1: Production of negative electrode An active material was prepared, which included artificial graphite in the form of secondary particles formed by granulating primary particles of artificial graphite, and a carbon coating layer disposed on the artificial graphite. In this case, the D50 of the primary particles in the active material was 10 μm, and the average particle size (D50) of secondary particles formed by granulating and agglomerating the primary particles was 20 μm. The carbon coating layer on the secondary particles was included in an amount of 4.0 wt % based on the total weight of the second active material. In this case, the average particle size (D50) of the secondary particles on which the carbon coating layer was formed was 21 μm.

[0105] The active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:1:2:1, and water was added to prepare a slurry.

[0106] The slurry was applied to one side of a 10 μm thick negative electrode current collector made of copper (Cu) foil at a rate of 5 mAh / cm. 2 After coating the slurry, it was dried at 80°C for 20 minutes to remove water in the slurry, and the dried slurry layer was rolled and then vacuum dried at about 130°C for 8 hours to prepare a negative electrode. At this time, the porosity of the prepared negative electrode was 30%.

[0107] The negative electrode thus manufactured had a total thickness of 100 μm. Single layer The negative electrode active material layer had a structure.

[0108] Comparative Example 2: Production of negative electrode Primary particles of artificial graphite with an average particle size (D50) of 10 μm were used as the active material.

[0109] The active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:1:2:1, and water was added to prepare a slurry for the lower layer.

[0110] The slurry was applied at 5 mAh / cm2 to one side of a 10 μm thick negative electrode current collector made of copper (Cu) foil. 2 After coating the slurry, it was dried at 80°C for 20 minutes to remove water in the slurry, and the dried slurry layer was rolled and then vacuum dried at about 130°C for 8 hours to prepare a negative electrode. At this time, the porosity of the prepared negative electrode was 30%.

[0111] The negative electrode thus manufactured had a total thickness of 100 μm. Single layer The negative electrode active material layer had a structure.

[0112] Comparative Example 3: Production of negative electrode The first active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a first binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:1:2:1, and water was added to prepare a lower layer slurry. The second active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:1:2:1, and water was added to prepare an upper layer slurry. The negative electrode was manufactured in the same manner as in Example 1.

[0113] Comparative Example 4: Production of negative electrode A negative electrode was prepared in the same manner as in Example 1, except that the second active material did not include a carbon coating layer.

[0114] Comparative Example 5: Production of negative electrode A negative electrode was prepared in the same manner as in Example 1, except that the first active material carbon coating layer was provided.

[0115] At this time, the carbon coating layer was included in an amount of 4.0 wt % based on the total weight of the first active material.

[0116] Comparative Example 6: Production of negative electrode A negative electrode was produced in the same manner as in Example 1, except that the upper layer slurry of Example 1 was used as the lower layer slurry, and the lower layer slurry of Example 1 was used as the upper layer slurry.

[0117] Comparative Example 7: Production of negative electrode A secondary particle-type artificial graphite (without a carbon coating layer) formed by granulating primary particles of artificial graphite was prepared as a first active material. In this case, in the first active material, the primary particles had a D50 of 10 μm, and the average particle size (D50) of the secondary particles formed by granulating and agglomerating the primary particles was 20 μm.

[0118] The first active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a second binder polymer, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 95:1:3:1, and water was added to prepare a slurry for the lower layer.

[0119] A negative electrode was manufactured in the same manner as in Example 1, except that the prepared lower layer slurry was used.

[0120] Negative electrode / secondary battery characteristic evaluation Experimental example 1: Battery quick charging performance evaluation 1.7671cm 2 The lithium (Li) metal thin film cut into a circular shape was used as a positive electrode. A porous polyethylene separator was interposed between the positive electrode and the negative electrode (negative electrodes of Examples 1 to 3 and Comparative Examples 1 to 7), and an electrolyte in which 0.5 wt% vinylene carbonate was dissolved in a mixed solution of methyl ethyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 7:3 and LiPF6 was dissolved at a concentration of 1M was injected to prepare a lithium coin half-cell.

[0121] The fabricated half cell was charged in CC / CV mode (current rate of 0.1C, 5mV, 0.005C current cut-off) for the first three cycles and discharged to 1.0V in CC mode. Using the discharge capacity of the third cycle as a reference, it was charged to 80% SOC at a current rate of 1.5C in CC mode and the voltage as a function of SOC change was plotted as a graph. The graph shows SOC on the X axis and the measured output voltage on the Y axis, and the fast charge performance was evaluated by finding the change point of the slope by dV / dQ differentiation to determine the Li plating SOC.

[0122] Experimental Example 2: I(004) / I(110) during X-ray diffraction analysis For each of the negative electrodes of Examples 1 to 3 and Comparative Examples 1 to 7, an X-ray diffraction analysis was performed using an XRD device to confirm the peak intensity of each of the (004) and (110) planes, and the value of I(004) / I(110), which is the ratio of the peak intensity of the (004) plane to the peak intensity of the (110) plane, was calculated.

[0123] Experimental Example 3: Evaluation of negative electrode adhesive strength The negative electrode adhesive strength of each of the negative electrodes of Examples 1 to 3 and Comparative Examples 1 to 7 was evaluated by the following method, and the results are shown in Table 2.

[0124] The negative electrode was punched out to 20 mm x 150 mm and fixed to the center of a 25 mm x 75 mm glass slide using tape, and the current collector was peeled off using a UTM while measuring the 90° peel strength. The peel strength was measured for 5 or more pieces and averaged to evaluate the results.

[0125] [Table 2]

[0126] Referring to Table 2, it can be seen that the negative electrodes of Examples 1 to 3 have primary particles with excellent adhesion in the lower layer region, and artificial graphite with a secondary particle-type carbon coating layer with excellent fast charging in the upper layer region, and that the lower layer region has a higher content of binder polymer, resulting in excellent adhesion, and the upper layer region has a lower content of binder polymer, resulting in excellent fast charging. Meanwhile, the negative electrode of Comparative Example 1 uses artificial graphite with a secondary particle-type carbon coating layer. Single layer The adhesive strength was very low due to the manufacturing process, and the fast charging performance was deteriorated due to the content of the binder polymer in the upper layer region of Comparative Example 1 being higher than that of Example 1.

[0127] In the case of the negative electrode of Comparative Example 2, primary particle-type artificial graphite was used. Single layerThe binder polymer content in the lower layer region of Comparative Example 2 was smaller than that in Examples 1 to 3, resulting in a decrease in adhesive strength, and the degree of orientation was large, resulting in a significant decrease in fast charging performance.

[0128] In the case of the negative electrode of Comparative Example 3, the same active material as in Example 1 was used in the lower layer region and the upper layer region. However, since the content of the binder polymer in the lower layer region and the upper layer region was the same, the adhesive strength was reduced compared to the negative electrode of Example 1, and the fast charging performance was also reduced.

[0129] In the case of the negative electrode of Comparative Example 4, it was confirmed that the secondary particles in the upper layer region did not have a carbon coating layer compared to the negative electrode of Example 1, and therefore the rapid charging performance was deteriorated.

[0130] In the case of the negative electrode of Comparative Example 5, the primary particles used in the lower layer region were provided with a carbon coating layer compared to the negative electrode of Example 1, and the primary particles provided with a carbon coating layer had hard characteristics. When an active material provided with a carbon coating layer was used in both the upper and lower layer regions, it became difficult for pores to be formed in the upper layer region, and the diffusion resistance of the electrolyte increased, resulting in a decrease in fast charging performance.

[0131] In the case of the negative electrode of Comparative Example 6, the upper layer region and the lower layer region are reversed compared to the negative electrode of Example 1, and it is understood that the adhesive strength is also reduced and the rapid charging performance is also inferior.

[0132] In the case of the negative electrode of Comparative Example 7, compared to the negative electrode of Example 1, secondary particle-type artificial graphite was used in the lower layer region instead of primary particle-type artificial graphite, and as a result, the fast charging performance was partially improved, but the adhesive strength was very low, making it difficult to actually use.

Claims

1. A negative electrode current collector; a negative electrode active material layer including: a lower layer region located on at least one surface of the negative electrode current collector and including a first active material and a first binder polymer; and an upper layer region located on the lower layer region and including a second active material and a second binder polymer; the first active material is a primary particle of artificial graphite, the second active material is a secondary particle of artificial graphite and a carbon coating layer located on the secondary particle, a weight percentage of a first binder polymer in the lower layer region is greater than a weight percentage of a second binder polymer in the upper layer region.

2. 2. The negative electrode of claim 1, wherein the first active material has a D50 of 3 μm to 20 μm.

3. 2. The negative electrode according to claim 1, wherein the second active material has a D50 of 5 μm to 35 μm.

4. 2. The negative electrode according to claim 1, wherein the secondary particles of artificial graphite are formed by granulating primary particles of artificial graphite.

5. 2. The negative electrode of claim 1, wherein the carbon coating layer of the second active material is present in an amount of 0.5 wt % to 10.0 wt %, based on the total weight of the second active material.

6. 2. The negative electrode of claim 1, wherein the ratio of the weight percentage of the first binder polymer in the lower layer region to the weight percentage of the second binder polymer in the upper layer region is from 1.1:1 to 5:

1.

7. 2. The negative electrode according to claim 1, wherein a ratio (wt%) of the first binder polymer in a lower layer region of the negative electrode active material layer is 2 to 4 wt%, and a ratio (wt%) of the second binder polymer in an upper layer region of the negative electrode active material layer is 0.5 to 2 wt%.

8. 2. The negative electrode according to claim 1, wherein the total weight percentage of the first binder polymer and the second binder polymer is 1 to 3% by weight based on the entire negative electrode active material layer.

9. preparing a lower layer slurry including a first active material, a first binder polymer, and a first dispersion medium, and an upper layer slurry including a second active material, a second binder polymer, and a second dispersion medium; coating one surface of a negative electrode current collector with the lower layer slurry, and coating the upper layer slurry on the lower layer slurry; and drying the coated lower layer slurry and the coated upper layer slurry simultaneously to form a negative electrode active material layer. the first active material is a primary particle of artificial graphite, the second active material is a secondary particle of artificial graphite and a carbon coating layer located on the secondary particle, A method for producing a negative electrode, wherein the weight percentage of the first binder polymer in the solid content of the underlayer slurry is greater than the weight percentage of the second binder polymer in the solid content of the overlayer slurry.

10. 10. The method for producing a negative electrode according to claim 9, wherein a ratio of the weight percentage of the first binder polymer in the solid content of the lower layer slurry to the weight percentage of the second binder polymer in the solid content of the upper layer slurry is 1.1:1 to 5:

1.

11. 10. The method for producing a negative electrode according to claim 9, wherein the weight percentage of the first binder polymer in the solid content of the lower layer slurry is 2 to 4 weight percent, and the weight percentage of the second binder polymer in the solid content of the upper layer slurry is 0.5 to 2 weight percent.

12. 10. The method for producing a negative electrode according to claim 9, wherein a total ratio (wt %) of the first binder polymer and the second binder polymer to a total solid content of the lower layer slurry and the upper layer slurry is 1 to 3 wt %.

13. A lithium secondary battery comprising the negative electrode according to claim 1 .

Citation Information

Patent Citations

  • Lithium ion secondary battery

    JP1999126600A

  • Electrode for nonaqueous electrolyte secondary battery and method for manufacturing the same, and nonaqueous electrolyte secondary battery

    JP2011192539A

  • Negative electrode for lithium secondary battery and lithium secondary battery containing the same

    JP2015511389A

  • Negative electrode and lithium secondary battery comprising the negative electrode

    KR1020200073801A

  • Negative electrode active material for lithium secondary battery, negative electrode including the same, and lithium secondary battery including the negative electrode

    US20190198857A1